The Implementation of Industrial Work Culture as an Effort to Educate Students' Character in Qualitative Analysis Practical Learning for Grade XI of Analytical Chemistry Department at SMTI Yogyakarta Vocational School - Quari, Triana Quari Sedyasthi (IJCER (International Journal of Chemistry Education Research), 2024)
This research aims to implement industrial work culture as an effort to educate students' character in practical learning of Qualitative Analysis for grade XI of Analytical Chemistry Department at SMTI Yogyakarta Vocational School. The research was carried out with a qualitative approach to survey results for students after completing the learning process with a block system lesson schedule, where students must comply with rules or regulations that instill discipline, responsibility and tough character. Students are required to submit practical reports within a certain time limit. The subjects in this research were eleventh-grade students of Analytical Chemistry Department at SMTI Yogyakarta Vocational School, totaling 32 students. The data were analyzed descriptively and present in tabular form. The results of the research showed that the majority agreed with the statements in the questionnaire given, where in the results of the evaluation survey of the block system learning schedule, 68.75% agreed that practical learning with the block system could improve student discipline and 31.25% strongly agreed. 59.38% agreed that practical learning with the block system could increase student’s endurance (physical and mental endurance) and 34.38% strongly agreed. 50.00% agreed that practical learning with the block system could train students to manage time and 43.75% strongly agreed. 46.88% agreed that practical learning with the block system could increase student learning motivation and 21.88% strongly agreed. 65.63% agreed that practical learning with the block system could further facilitate student’s level of understanding and 15.63% strongly agreed. Meanwhile, in the survey results regarding the rules for collecting practice reports with a certain time limit, 56.25% agreed that collecting practice reports with a certain time limit could improve student discipline and 31.25% strongly agreed. 59.38% agreed that collecting practice reports with a certain time limit could increase student’s endurance (physical and mental endurance) and 34.38% strongly agreed. 59.38% agreed that practical learning with the block system could train students to manage time and 28.13% strongly agreed. 46.88% agreed that practical learning with the block system could increase student learning motivation and 21.88% strongly agreed. Therefore, it can be concluded that the implementation of industrial work culture in the practical learning for grade XI of Analytical Chemistry Department at SMK-SMTI Yogyakarta Vocational School can be a character education effort, which is supported by the survey results, where the majority agreed with the statements in the questionnaire given to student representatives who were the objects of research